2013
DOI: 10.1093/cercor/bht235
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Recordings of Human Neocortical Oscillations

Abstract: Electrophysiological oscillations are thought to create temporal windows of communication between brain regions. We show here that human cortical slices maintained in vitro can generate oscillations similar to those observed in vivo. We have characterized these oscillations using local field potential and whole-cell recordings obtained from neocortical slices acquired during epilepsy surgery. We confirmed that such neocortical slices maintain the necessary cellular and circuitry components, and in particular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
63
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 116 publications
9
63
3
Order By: Relevance
“…Modeling of this metric has revealed that information transfer (transfer entropy) is correlated to the strength of PDPC (Buehlmann and Deco, 2010), suggesting that the coherent theta oscillation we observe here may subserve information transfer between cortical laminae in vivo. Furthermore, axonal delays determine the strength, shape, and optimal frequency at which PDPC is operative (Eriksson et al, 2011), suggesting that a complex bilaminar theta resonant structural circuit motif (Womelsdorf et al, 2014) may underlie our observations. Such interlaminar interactions have been described for alpha oscillations within the occipital lobe (Bollimunta et al, 2008;Spaak et al, 2012), although the analogy to alpha activity in macaque inferotemporal cortex is likely more appropriate given its association with increased multiunit firing rather than inhibition (Mo et al, 2011).…”
Section: Discussionmentioning
confidence: 70%
“…Modeling of this metric has revealed that information transfer (transfer entropy) is correlated to the strength of PDPC (Buehlmann and Deco, 2010), suggesting that the coherent theta oscillation we observe here may subserve information transfer between cortical laminae in vivo. Furthermore, axonal delays determine the strength, shape, and optimal frequency at which PDPC is operative (Eriksson et al, 2011), suggesting that a complex bilaminar theta resonant structural circuit motif (Womelsdorf et al, 2014) may underlie our observations. Such interlaminar interactions have been described for alpha oscillations within the occipital lobe (Bollimunta et al, 2008;Spaak et al, 2012), although the analogy to alpha activity in macaque inferotemporal cortex is likely more appropriate given its association with increased multiunit firing rather than inhibition (Mo et al, 2011).…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, spontaneous seizure‐like events appeared in neocortical slices derived from epileptic patients, by applying kainate plus carbachol (Florez et al . ), as well as in the Mg 2+ ‐free model (Avoli et al . ; Mattia et al .…”
Section: Introductionmentioning
confidence: 99%
“…During the course of the seizures, heterogeneous firing patterns were detected in both the human hippocampus (Babb et al 1987) and the neocortex, together with a high ratio of cells increasing their firing rate (Truccolo et al 2011). Furthermore, spontaneous seizure-like events appeared in neocortical slices derived from epileptic patients, by applying kainate plus carbachol (Florez et al 2015), as well as in the Mg 2+ -free model (Avoli et al 1987;Mattia et al 1995), with such seizures being reflected intracellularly as a large depolarizing shift and burst firing (Avoli et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Rhythmic brain activity supports the packaging and segmentation of information, and its coordination across distant brain areas. More recently, brain rhythms at different frequency bands were found to interact with each other2930, a process called “cross-frequency coupling” (CFC) that has attracted increasing interest. One subtype of CFC, phase-amplitude coupling (PAC), has been particularly noteworthy.…”
mentioning
confidence: 99%